MRCS applied basic science and clinical topics - Parker, Stephen (London : JP Medical Publishers, 2013)
MRCS Applied Basic Science and Clinical Topics offers a complete and up-to-date guide to specialty training in surgery, covering the core topics examined in the MRCS Part A and B exams
Includes index
Keywords: General Surgery; Examination Questions